GAMBARAN MEKANISME KOPING KELUARGA SELAMA MENDAMPINGI PASIEN DI RUANG INTENSIF: LITERATURE REVIEW - Abdul Khoiruddin; Gamya Tri Utami; Erwin Erwin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
Background: Patients undergoing treatment in intensive care unit have several needs: physical comfort, safety, being respected as an individual, emotional support, information, privacy, family involvement, friends, and decision making. To fulfill all those needs, supports from family members are vitally needed. Purpose: The aim of this study was to determine family coping mechanism during assisting patients in intensive care unit based on existing literature. Methodology: The method applied in this study was literature review, conducted by acquiring and reviewing full, related scientific study articles published between the year 2016 and 2020 using Science Direct and Google Scholar, the key phrases used were “Mechanism Coping Family for Assisting Patients in Intensive.” The articles were then selected using PICO. Result: After carefully reviewing 7 related journal articles, in 6 articles, it was found that most families used adaptive coping mechanism while assisting patients in intensive care unit, whereas in 1 journal article, it was found that most families applied maladaptive coping mechanism. Conclusion: There are two types of family coping mechanisms applied while assisting patients in intensive care unit: adaptive and maladaptive. It is suggested that family should apply adaptive coping mechanism while assisting their family members in intensive care unit. Keywords: Family Coping Mechanism, Patients in Intensive Care Unit.